Microenterprises Statistics – Organization of the Annual Survey of Economic Activity of Enterprises and Its Results in the Years 2009–2021 - Mikulec, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
After introducing the specialization of Statistical Offices in 2009 – assigning specialized nationwide tasks, performed as part of the activity aimed at official statistics as a whole – the Statistical Office in Łódź (SO in Łódź) became responsible for the implementation of tasks, among others, in the field of small and medium‑sized enterprises statistics. The SO in Łódź prepared and conducted an annual survey of economic activity of enterprises (SP–3) and a panel survey of enterprises (PL1, PL2) throughout the country. In the following years some serious changes occurred in the above mentioned research. The aim of the paper is to familiarize readers and users of statistical data with both theoretical and practical aspects of conducting statistical research in the area of non‑finance enterprises. The paper is addressed to individuals interested in the methodology of statistical research, statistical reporting (of entities), or to those who deal with data analysis in the sector of small (including micro) and medium‑sized enterprises. The first part of the paper, which is of methodical character, includes detailed information on the organization of selected annual statistical research on non‑finance enterprises, in particular information related to microenterprises. The whole range of problems of the SP–3 survey was discussed together with the changes which occurred in this research throughout the whole analysed period – among others, the process of surveys integration (PL1, PL2 and KZ surveys). The second part of the paper is of empirical character and it contains selected results of economic activity of enterprises with up to 9 persons employed in 2020 (research conducted in 2021) in relation to the results obtained by microenterprises in previous years. The final part of the paper stresses the importance of data obtained from SP–3 survey and its ability to satisfy a wide range of information needs.